Stiffness changes in internal rotation muscles of the shoulder and its influence on hemiplegic shoulder pain - Jia, Fan; Zhu, Xin-Rui; Kong, Ling-Yu; Fan, Jie-Cheng; Zhu, Zong-Jing; Lin, Li-Zhen; Zhang, Shu-Yun; Yuan, Xiang-Zhen (Frontiers in Neurology, 2023)
Background Hemiplegic shoulder pain (HSP) is a common complication in patients with stroke. The pathogenesis of HSP is complex, and muscle hypertonia, especially the hypertonia of internal rotation muscles of the shoulder, may be one of the important causes of shoulder pain. However, the relationship between muscle stiffness and HSP has not been well studied. The purpose of this study is to explore the correlations between the stiffness of internal rotation muscles and clinical symptoms in patients with HSP. Methods A total of 20 HSP patients and 20 healthy controls were recruited for this study. The stiffness of internal rotation muscles was quantified using shear wave elastography, and Young's modulus (YM) of the pectoralis major (PM), anterior deltoid (AD), teres major ™, and latissimus dorsi (LD) were measured. Muscle hypertonia and pain intensity were evaluated using the Modified Ashworth Scale (MAS) and Visual Analog Scale (VAS), respectively. The mobility of the shoulder was evaluated using the Neer score. The correlations between muscle stiffness and the clinical scales were analyzed. Results YM of internal rotation muscles on the paretic side was higher than that of the control group in the resting and passive stretching positions (P < 0.05). YM of internal rotation muscles on the paretic side during passive stretching was significantly higher than that at rest (P < 0.05). YM of PM, TM, and LD during passive stretching were correlated with MAS (P < 0.05). In addition, the YM of TM during passive stretching was positively correlated with VAS and negatively correlated with the Neer score (P < 0.05). Conclusion Increased stiffness of PM, TM, and LD was observed in patients with HSP. The stiffness of TM was associated with pain intensity of the shoulder and shoulder mobility.